Pengalaman Kewartawanan Perempuan dalam Mendapatkan Kesetaraan Karir di Media Massa - Irsyadiah, Uli Zahro; Hasfi, Nurul; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Journalism is a high-risk profession, often associated with men. Women who enter this field face numerous obstacles, particularly at the organizational level, which affects their career development opportunities. This study aims to understand the experiences of female journalists in achieving career equality in the mass media, both in performing their duties and in policies related to their career sustainability. The main theories and concepts used in this study are standpoint theory, liberal feminism, and gender organizational communication. This descriptive research employs a critical phenomenology design and a critical paradigm. The subjects of this study are six journalists from print, online, and television media, categorized as junior, mid-level, and senior journalists. The results of this study highlight significant challenges such as the double burden, gender stereotypes, labor exploitation through assignments outside their job description, and centralized management policies. In local media, centralized policy systems can hinder the careers of regional journalists, reducing their chances of advancing to managerial positions or gaining recognition for their contributions compared to their colleagues at headquarters. These challenges make it difficult for female journalists to sustain their careers, prompting efforts such as skill development, adaptation to the work environment, networking, and proving themselves through their work.